Empowerment of Karawitan in : Social Communication Media of Lidah Kulon Lakarsantri Community Surabaya - Tiara, Biyanca; Sugito, Tomy Agung (Solah, 2025)
This study discusses the empowerment of karawitan as a medium of social communication in the Lidah Kulon community, Lakarsantri District, Surabaya City. Karawitan, as one of Javanese cultural heritages, not only functions as a means of entertainment, but also has social, educational, and spiritual values ​​that can strengthen inter-community communication. Through a qualitative-descriptive approach, this study reveals how local karawitan groups in Lidah Kulon are empowered as a medium for conveying moral messages, preserving culture, and increasing social cohesion. The results of the study show that karawitan activities actively involve various levels of society, from the younger generation to community leaders, so that a harmonious social interaction space is created. In addition, the use of karawitan in traditional, religious, and community events shows its effectiveness in building inclusive and sustainable social communication. Thus, the empowerment of karawitan has proven to be a relevant cultural strategy in strengthening local identity while building social solidarity in urban communities.